Determinants of borrowers’ intentions on educational loan repayment in Malaysia: an empirical investigation / Shafinar Ismail … [et al.] - Ismail, Shafinar; A Razak, Nur Atiqah; Shaidin, Sumayyah; Mohd Rafien, Nor Shahrina; Ismail, Suzila (Center for Islamic Philanthropy and Social Finance (CIPSF), 2021)
Most students from lower-income families would apply for an education loan when they enroll in higher academic universities. As the number of loans has risen, students' capability to make repayment on their loans has also risen and thus caused problems. Therefore, this study will look over the determinants of students' intention on their education loan repayment among final year undergraduates. Questionnaires were distributed to the 111 students in the universities. The sampling method applied in this study was purposive sampling. The survey was created in two parts, one consisting of demographic information and the next part relating to the determinants of intention to repay education loans. The results revealed significant relationships between attitude towards loan repayment and intention to repay education loan and knowledge about loan agreement to repay their education loan. However, the relationship between perceptions that loan repayment will affect quality of life after graduation and intention to repay the education loan and perceptions towards loan agreement and intention to repay education loan were not supported. This study improves present understanding by exploring and explaining further on a few crucial elements related to students' intention to repay their education loan. This study describes the effects of attitude, perceptions and the importance of knowing about loan agreement. This study is one of the first to look into the determinants of students' intention to repay education loans that include loan agreement.